Keanekaragaman Jenis Gastropoda di Hutan Mangrove Desa Ranga-Ranga Kecamatan Masama Kabupaten Banggai - Wahyudin Abdul Karim; Sulasmi Anggo; Hairunnisa Japri Soden (Bioscientist : Jurnal Ilmiah Biologi, 2021)
Gastropods are one of the biological natural resources that have high diversity in the mangrove ecosystem. The purpose of this study was to determine the diversity of gastropod species in the mangrove forest of Ranga-Ranga Village, Masama District, Banggai Regency. This type of research is descriptive quantitative. The research was conducted from August to September 2020 in the mangrove forest of Ranga-Ranga Village. The data collection technique used a 100 m perpendicular line transect, then along the line transect there were 5 plots with a size of 10 m x 10 m, and the distance between plots was 10 m. Data collection was carried out once in each plot. The data analysis technique used the Shannon-Wienner diversity index analysis. The results showed that there were 7 species of gastropod found, namely: Telescopium telescopium, Faunus ater, Ellobium aurisjudae, Neritina sp., Cerithidea cingulata, Cassidula aurifelis, and Chicoreus capucinus. The results of the calculation of the gastropod diversity index in plot I are 1.35086, plot II is 1.48419, plot III is 1.50932, plot IV is 1.51415, and plot V is 1.45345, with a total diversity index of 1.419058. This shows that the index of gastropod diversity in the mangrove forest of Ranga-Ranga Village, Masama District, Banggai Regency is included in the medium category.